The influence of the bobath method in the treatment of children with Down Syndrome: a systematic review (Research, Society and Development, 2022)
Introduction: Down Syndrome (DS) represents a chromosomal anomaly, due to an alteration in the chromosome of the pair 21. Carriers of this syndrome present particular phenotypic characteristics, in addition to changes in motor and cognitive development, which will require physiotherapeutic care. In this public, the physiotherapeutic intervention is considered of extreme relevance for child development, making use of several techniques, including the Bobath method. Objective: To report, through studies, whether the Bobath method is effective in physiotherapeutic treatment for the neuropsychomotor development of children with DS. Methodology: This study is a systematic review, with data collection carried out in the LILACS, PubMed, SciELO and CAPES Periodicals databases in Spanish, Portuguese and English, including studies from the year 2010. Using as search strategy the words Down Syndrome, Bobath Method, Motor development, Physical therapy modalities, in a combined and isolated way. Results: Finding a total of 24,043 studies, 21 were selected, due to contain one of the keywords in its title, better describe the physiopathology of DS, address the Bobath method and its therapeutic effects on the syndrome described. Conclusion: Despite the few studies describing the techniques of the Bobath method, research with a control group seeking to compare the effectiveness of the method as a physiotherapeutic intervention in DS, significant progress can be observed in the child's evolutionary picture throughout his motor acquisitions, although there is a need for more studies to be published in order to fill the gaps existing about the method in the DS public.